House Of Cards : Baseball Card Collecting and Popular Culture - Bloom, John, 1962- (Book collections on Project MUSE., 1997)
From interviews with collectors, dealers, and hobbyists as well as analyses of the baseball card industry and extensive firsthand observations, John Bloom explores what this hobby tells us about nostalgia, work, play, masculinity, and race and gender relations among collectors.